Development of Trade and Investment Cooperation in Greater Mekong Sub-region: Thailand, Lao PDR, Vietnam, and Cambodia - Mephokee, Chanin; Roopsom, Tananat; Klinsukhon, Chotipat (Thai Journal of East Asian Studies, 2015)
This research aims to study on the trade and investment development among Greater Mekong Sub-region (GMS) countries, including Cambodia, Laos, Thailand, and Vietnam. Recently this sub-region has played more positive roles in terms of economic development and in international economic cooperation. For the first section, the gravity model is employed to explain the factors affecting the trade between Thailand and countries in GMS. The research found that Gross Domestic Products (GDP) of each country, tariff rates, trade facilities, and distance between countries are able to explain the trade value between Thailand and GMS countries. The second section of the research explains the factors affecting foreign direct investment (FDI) inflows to Thailand and to Vietnam. By using ARIMAX model, the study found that GDP per Capita, real interest rates, and degree of openness can be the leading indicators for FDI. For Vietnam, exchange rate is the additional variable that can be leading indicator for FDI. The third section of this research is the study on the effects of Thailand-Cambodia economics cooperation under the ACMECS framework. The study found that the infrastructure development under ACMECS provides the positive opportunities for Thai investors to invest in Cambodia. The study suggests that there are some industries that Thai investors may have comparative advantages in investment, such as, construction, tourism, drinking water, garments, and medical services. These are markets with high domestic demand but lacks of domestic supply.